Social Construction of Parents Against Child Labor in Tobacco Farming in Wakan Village, East Lombok Regency - M. Arif Budiman Hakim; Drajat Tri Kartono; Eny Lestari (Universitas Lambung Mangkurat, 2025)
Child labor in the tobacco sector remains a critical problem in Indonesia, especially in rural areas. In Wakan Village, East Lombok, children are generally involved in tobacco farming due to entrenched economic pressures and local norms. This study aims to analyze how parents socially construct the meaning of child labor in tobacco farming. A qualitative case study approach is used. Data was collected through in-depth interviews with parents and community leaders, hands-on field observations, and documentation. These findings reveal that children aged 10-15 years are actively involved in three main stages of tobacco production: fertilization (berabok), leaf binding (begelantang), and drying (bejelok). These tasks expose children to risks such as exposure to chemicals, physical strain, and school disruptions. Economic needs shape parents' perceptions, inherited social norms, and the belief that early work builds responsibility. The results show that child labor is not only driven by poverty, but also by cultural constructions that normalize and legitimize children's participation in agriculture. This study demonstrates the importance of community-based empowerment approaches rooted in local values to reduce child labor practices. Collaborative efforts are essential to raise awareness, challenge traditional beliefs, and protect children's rights in rural farming communities.